Transcriptome analysis reveals immune and metabolic regulation effects of Poria cocos polysaccharides on Bombyx mori larvae - Liu, Jiajie; Hong, Wanyu; Li, Mei; Xiao, Yang; Yi, Yunhong; Liu, Yi; Wu, Gongqing (Frontiers in Immunology, 2022)
Poria cocos polysaccharides (PS) have been used as Chinese traditional medicine with various pharmacological effects, including antiviral, anti-oxidative, and immunomodulatory activities. Herein Bombyx mori silkworm was used as a model animal to evaluate the immunomodulatory effects of PS via detecting the changes of innate immune parameters and explore the underlying molecular mechanism of the immunoregulatory effect of PS using Illumina HiSeq Xten platform. The results presented here demonstrated that a hemocoel injection of PS significantly enhanced the cellular immunity of silkworm, including hemocyte phagocytosis, microaggregation, and spreading ability. A total of 335 differentially expressed genes (DEGs) were screened, including 214 upregulated genes and 121 downregulated genes by differential expression analysis. Gene annotation and enrichment analyses showed that many DEGs related to immune signal recognition, detoxification, proPO activation, carbohydrate metabolism, and lipid metabolism were significantly upregulated in the treatment group. The Kyoto Encyclopedia of Genes and Genomes-based Gene Set Enrichment Analysis also revealed that the more highly expressed gene sets in the PS treatment silkworm were mainly related to immune signal transduction pathways and energy metabolism. In addition, the activity of four enzymes related to immunity and energy metabolism—including phenoloxidase, glucose-6-phosphate dehydrogenase, hexokinase, and fatty acid synthetase—were all significantly increased in the larvae injected with PS. We performed qRT-PCR to examine the expression profile of immune and metabolic-related genes, which further verified the reliability of our transcriptome data and suggested that PS can regulate the immunity of silkworm by enhancing the cellular immunity and modulating the expression levels of genes related to immune responses and physiological metabolism. These findings will lay a scientific foundation for the use of PS as an immunomodulator in disease prevention in human beings or animals.